Motherly Affection and the Question of Poverty: A Comparative Study of ‘Lady Audley’s Secret’ and ‘Someone Else’s Child’ - Roohollah Roozbeh (International Journal of English Language and Translation Studies, 2017)
This article considers Jalal Al-Ahmad and Elizabeth Braddon as writers whose fictions voiced attitudes towards poverty and motherhood. Two women, to get rid of poverty, have to get rid of their children in order to remarry. These two women consider remarriage as their only way to happiness and each one deems her child as an obstacle and gives up her motherly affection for her child. The study of this common subject in two different cultures is justifiable from the theory of comparative literature. Thus, aim of this paper is to examine these two English and Persian works from the theory of confluence so as to show the differences and similarities. The method of this paper is based on comparative literature ofَ American School which regards confluence as point of investigation and does not deem direct influence of one author on another as a point of departure. That the two authors have used one similar subject is a condition for their study and comparison in this school.